Faith, Tolerance, and National Identity: Rethinking Character Education in a Multicultural Society - Qodratulloh S, Waway; Rafdinal, Wahyu; Hazma, Hazma; Nurasman, Muhammad Syaiful; Anwar, Saepul; Umar, Mardan (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study aims to investigate the impact of religious character on the development of students' social and national identities in higher education, encompassing tolerance, patriotism, politeness, nationalism, and cultural openness. The research employed a quantitative approach, involving an online survey of 1,025 students from three public universities in West Java. Data were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). The findings show that religious character significantly influences patriotic character (β = 0.653, f² = 0.744), tolerant character (β = 0.317, f² = 0.134), and polite character (β = 0.132, f² = 0.028). Patriotic character, in turn, has the most potent effect on nationalistic character (β = 0.841; f² = 2.426), which significantly influences culturally respectful character (β = 0.558). The model also confirms that the influence of religious character on nationalism and cultural openness is indirect, mediated through patriotic and nationalistic characters. These results highlight the sequential and integrative formation of national character, beginning with the internalization of spiritual values and extending to inclusive civic attitudes. The model makes a theoretical contribution to the character education discourse and supports the design of curricula that integrate religiosity and national values to address identity fragmentation in multicultural societies.